Análise dos polimorfismos RS1800871 e RS1800872 do gene da interleucina 10 em indivíduos diagnosticados com esquizofrenia - Lopes, Alice Tâmara de Carvalho (2019)
Schizophrenia is an neurocognitive disorder that affects about 1% of the population. Evidence shows that increases in the risks of the onset of schizophrenia (EQZ) and other neuropsychiatric disorders are due to the imbalance of pro and antiinflammatory agents associated with environmental and genetic components. Cytokines are the major regulators of inflammatory immune reactions and brain development and emerge as a common pathway for elucidation of the disease. This study aims to evaluate whether there is an association between the rs1800871 and rs1800872 polymorphisms of IL-10 gene and the susceptibility to the development of schizophrenia by detection of polymorphisms (SNPs) by Sanger sequencing technique in individuals giagnosed with EQZ in Goiânia, Goiás. Samples were collected from 156 individuals, 95 individuals diagnosed with EQZ (case group) and 61 healthy individuals with no history of psychosis (control group). There isn’t association between rs1800871 (p=0.97) and rs1800872 (p=0.83) SNPs and the susceptibility to the development of EQZ. There was prevalence of smoking, alcohol use and chemical dependency (p<0.001). The haplotype T/A had a higher frequency in the case group (0,2).